Reduced expression of αGlcNAc in Barrett's oesophagus adjacent to Barrett's adenocarcinoma – a possible biomarker to predict the malignant potential of Barrett's oesophagus. Issue 4 (23rd November 2013) - Iwaya, Yugo; Hasebe, Osamu; Koide, Naohiko; Kitahara, Kei; Suga, Tomoaki; Shinji, Akihiro; Muraki, Takashi; Yokosawa, Shuichi; Yamada, Shigenori; Arakura, Norikazu; Tanaka, Eiji; Nakayama, Jun
<x xml:space="preserve">Abstract</x> Aims Gastric gland mucin contains O‐glycans exhibiting terminal α1, 4‐linked N‐acetylglucosamine residues (αGlcNAc). Recently we demonstrated that mice deficient in αGlcNAc in gastric gland mucin develop gastric adenocarcinoma spontaneously, indicating that αGlcNAc is a tumour suppressor for gastric cancer. However, the role of αGlcNAc in Barrett's oesophagus (BO) remains unknown. In this study, we investigated whether reduced αGlcNAc expression in BO is associated with development of Barrett's adenocarcinoma (BAC). Methods and results Thirty‐five BO lesions adjacent to BAC were examined by immunohistochemistry for αGlcNAc, MUC6 and CDX2. As controls, 35 BO lesions without BAC obtained from patients with oesophageal squamous cell carcinoma were also analysed. Expression of αGlcNAc relative to its scaffold MUC6 in BO adjacent to BAC was reduced significantly compared to control BO. Decreased αGlcNAc expression in BO adjacent to BAC was particularly significant in patients with smaller tumour size (<20 mm) and minimal invasion of tumour cells to the superficial muscularis mucosae. There was also a significant inverse correlation between αGlcNAc and CDX2 expression in BO adjacent to BAC. Conclusions Decreased expression of αGlcNAc compared with MUC6 in BO is a possible hallmark in predicting BAC development.